Problem-solving ability of high school students: Preliminary study analysis using rasch modeling - Syifa, Annisa; Azizah, Anisa Nur; Fardanti, Aribah Chika; Rahayu, Fatonah; Indratno, Toni Kus; Sukarelawan, Moh. Irma; Abdullah, Nurul Syafiqah Yap (Education and Development Research, 2024)
One of the problems in learning physics is the weak ability of students to solve problems. Therefore, this study aims to conduct a preliminary study to recommend appropriate learning models. The type of research used is survey research. As many as 23 students were involved as primary data sources to determine the need for problem-solving skills. Respondents came from class XI of one of the state high schools in Yogyakarta. Problem-solving ability data was collected using 16 survey items formatted in the Google Form. Data analysis was performed using Rasch modeling. The analysis results show that there are limitations in students' problem-solving skills or abilities. Based on the survey results, it is recommended that the Problem base learning or guided inquiry model can be an alternative to optimizing students' problem-solving abilities.